Preparation and characterization of topical solid lipid nanoparticles containing deferoxamine - Behzad Sharif Makhmalzade; Masoud Ali Karami; Narges Mosaddegh Rad (Facultad de Farmacia, Universidad de Granada, 2021)
Abstract Introduction: Deferoxamine mesylate increases hypoxia inducible factor-1 alpha transactivation by preventing iron-catalyzed reactive oxygen stress, so it can be used to improve diabetic ulcer healing. This study was undertaken to develop and study physicochemical properties of topical deferoxamine-loaded solid lipid nanoparticles. Method: Solid lipid nanoparticles were prepared using cold homogenization technique and full factorial design to evaluate the effect of surfactant type and amount of lipid. In-vitro characterization of formulations including particle size and distribution, thermal behavior using Differential Scanning Calorimetry, entrapment efficiency, and release profile were carried out. Results: The results showed an acceptable range of particle size (2.88-174 nm), a narrow size distribution, and an average of 60% for drug entrapment efficiency which is significant for a hydrophilic drug. The results from release study showed an initial burst release followed by a slow and prolonged manner. Differential Scanning Calorimetry results also confirmed the results obtained from loading and release evaluations. The best formulation which had a high level of drug loading and the lowest drug release rate contained compritol and oleic acid in the amount of 8% of the total formula, as well as tween 80 and lecithin as a mixture of surfactants. Conclusions: The study demonstrated deferoxamine could be loaded in solid lipid nanoparticles to deliver topically.